Brain Abscesses in Domestic Ruminants: Clinicopathological and Bacteriological Approaches - Ferreira, Lucas Vinícius de Oliveira [UNESP]; Rocha, Thaís Gomes [UNESP]; Takahira, Regina Kiomi [UNESP]; Laufer-Amorim, Renée [UNESP]; Machado, Vânia Maria de Vasconcelos [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Pereira, Wanderson Adriano Biscola [UNESP]; Oliveira-Filho, José Paes [UNESP]; Borges, Alexandre Secorun [UNESP]; Amorim, Rogério Martins [UNESP] (MDPI, 2024)
Brain abscesses in ruminants often arise from primary infection foci, leading to an unfavorable prognosis for affected animals. This highlights the need for comprehensive studies on brain abscesses across different ruminant species. We retrospectively investigated medical records of epidemiological, clinical, neuroimaging, anatomopathological, and bacteriological findings in six ruminants (three goats, two cows, and one sheep) diagnosed with brain abscesses. All animals studied were female. Apathy (50%), compulsive walking (33%), decreased facial sensitivity (33%), head pressing (33%), seizures (33%), semicomatous mental status (33%), strabismus (33%), unilateral blindness (33%), and circling (33%) represented the most common neurologic signs. Leukocytosis and neutrophilia were the main findings in the hematological evaluation. Cerebrospinal fluid (CSF) analysis revealed predominant hyperproteinorrachia and pleocytosis. In three cases, computed tomography or magnetic resonance imaging were used, enabling the identification of typical abscess lesions, which were subsequently confirmed during postmortem examination. Microbiological culture of the abscess samples and/or CSF revealed bacterial coinfections in most cases. Advanced imaging examinations, combined with CSF analysis, can aid in diagnosis, although confirmation typically relies on postmortem evaluation and isolation of the causative agent. This study contributes to clinicopathological aspects, neuroimages, and bacteriological diagnosis of brain abscesses in domestic ruminants.
Keywords: bacterial infection; cerebrospinal fluid; computer tomography; livestock; magnetic resonance imaging; neurological disease